Marga Belitang Dalam Pemerintahan Onder Afdeeling Komering Ulu : Dinamika Sosial dan Budaya - Dewi, Nuriah Sinta; Rochmiatun, Endang; Padila, Padila (Tanjak: Sejarah dan Peradaban Islam, 2024)
This research is a local historical research that explains the Belitang clan in the Onder Afdeeling Komering Ulu government in terms of the history and social and cultural dynamics of the community. Marga is a form of government which is currently at the level of a sub-district and was established during the Dutch colonial government. The main issues are first, what is the history of the formation of the Belitang clan and second, what are the social and cultural dynamics of the Belitang clan community. This research is a qualitative descriptive research with data collection through observation, documentation, interviews and literature study. The results of this research conclude that (1) The origins of the Belitang clan began with the oldest hamlet in the area with residents who were descendants of the original Lampung Pepadun tribe. The community in the village is led by a clan balancer, namely Ratu Bagus Baginda, and lives in the Tanjung Raya Palace. He proposed the establishment of a clan government system in Belitang to the Dutch government and it was inaugurated in 1930 AD. (2) The social and cultural dynamics of the Belitang clan community have actually existed since the time of the Palembang Sultanate, for this reason the customary rules that apply in the community are almost the same as the rules mentioned in the Simbur Cahaya Law.